Percentage of Myeloid Dendritic Cells in Peripheral Venous Blood Is Negatively Related to Incidence of Graves' Orbitopathy. (27th January 2021) - Wojciechowska-Durczynska, Katarzyna; Wieczorek-Szukala, Katarzyna; Stefanski, Borys; Zygmunt, Arkadiusz; Stepniak, Jan; Karbownik-Lewinska, Małgorzata; Lewinski, Andrzej
Abstract : The aim of the study was to evaluate the distribution of blood dendritic cells (DCs) in patients with Graves' orbitopathy (GO) and to assess the influence of methylprednisolone therapy on subsets of peripheral blood mononuclear cells (PBMCs). Peripheral blood DC subsets were analyzed by flow cytometry in patients with active GO (n = 17 ), inactive GO (n = 8 ), and Graves' disease (GD) without GO (n = 8 ) and controls (n = 15 ); additionally, in patients with active GO (n = 17 ), analyses were done at three time points, i.e., before methylprednisolone treatment and after 6 weeks and after 12 weeks of the treatment. Percentage of myeloid DCs (mDCs) in PBMC fraction was significantly lower in patients with both active and inactive GO, compared to patients with GD without GO and controls (p < 0.05 ). In addition, mDCs were also documented to be an independent factor negatively associated with GO, however without essential differences between active and inactive phases. On the other hand, we did not observe any changes in the percentage of DCs after methylprednisolone therapy (p > 0.05 ). In the present study, we have succeeded to firstly demonstrate—according to our knowledge—that blood mDCs are negatively related to GO incidence.